Avaliação do potencial fitotóxico de frações e subfrações de folhas, cascas de caule e raízes de Ocotea pulchella e dos compostos salicilato de benzila e benzoato de benzila sobre espécies invasoras - Fuentes, Luis Felipe García (Universidade Federal de São Carlos, 2020)
Plants synthesize a wide variety of chemicals in response to biotic and abiotic stresses. These substances are usually associated with plant defense processes against herbivores and pathogens. These substances, derived from secondary metabolism are known as allelochemicals. The species of the Lauraceae family have the potential to produce secondary metabolites with herbicidal properties. Thus, the objective of this work was to evaluate the phytotoxic potential of extracts and subfractions of the species Ocotea pulchella, as well as of the synthetic compounds benzyl salicylate and benzyl benzoate on target species. For this, bioassays were carried out with coleoptiles of Triticum aestivum and bioassays of germination and initial growth of invasive species of agricultural crops. The concentrations of 0.8 mg.mL-1, 0.4 mg.mL-1 and 0.2 mg.mL-1 were used for hexane extracts, ethyl and aqueous acetates, of leaves, stem barks and roots as well as well as for the subfractions of the ethyl acetate extract of rainy season leaves from O. pulchella. For the synthetic compounds, concentrations of 10-3 M, 3•10-4 M, 10-4 M, 3•10-5 M and 10-5 M were used in bioassays with T. aestivum coleoptiles; whereas for the initial growth bioassays the concentrations of 10-3 M, 10-4 M e 10-5 M were used. All 18 extracts of O. pulchella inhibited the growth of T. aestivum coleoptiles at least in the highest concentration tested. In general, the group of ethyl acetate extracts (leaves, stem and root) from O. pulchella showed the highest phytotoxic activity in the target species. The benzyl salicylate and benzyl benzoate compounds showed strong inhibitory activity on the growth of T. aestivum coleoptiles, being even superior to the herbicide mainly at concentrations 3•10-5 M and 10-5 M. These compounds also showed an inhibitory effect on the bioindicator species Lactuca sativa, Solanum lycopersicum, Allium cepa and T. aestivum and on the invasive species Euphorbia heterophylla and Megathyrsus maximus. E. heterophylla was the species most affected by the action of both compounds in all evaluated parameters and in some parameters the inhibitory effect of these compounds was equal to that exerted by the herbicide, mainly in the root system. All eight subfractions obtained from the ethyl acetate extract of leaves from the rainy season significantly inhibited the growth of T. aestivum coleoptiles in the highest concentration (0.8 mg. ML-1) and seven of these also did in the other two concentrations (0, 4 mg. ML-1 and 0.2 mg. ML-1). In the initial growth bioassays, four subfractions were tested (A1, A2, A3 and A4) where subfractions A1 and A2 exerted the highest values of inhibition in the growth of the root and aerial part of the species E. heterophylla and M. maximus. In addition, in the species E. heterophylla, subfractions A1 and A2 exerted inhibition values statistically equal to those exerted by the herbicide in all concentrations tested both in the aerial part and in the root system. However, the highest concentration of subfraction A1 in the roots was higher than that observed by the herbicide at the same concentration. Thin layer chromatography was performed and the presence of benzyl salicylate and benzyl benzoate was verified in subfraction A1, such compounds are reported in the literature as compounds with phytotoxic potential responsible for the phytotoxic activity of O. pulchella. The reduction in the growth of the root system of E. heterophylla seedlings may be related to the decrease in the elongation of the metaxylem cells submitted to the subfractions of the ethyl acetate extract of leaves of the O. pulchella species. Therefore, it is possible to conclude that the O. pulchella species as well as the synthetic compounds benzyl salicylate and benzyl benzoate have phytotoxic potential.
Evaluation of the phytothoxic potential of fractions and subfractions of leaves, stem barks and roots of Ocotea pulchella and benzyl salicylate and benzyl benzoate compounds on invasive species
Keywords: Aleloquimicos; Cerrado; Herbicidas naturais; Espécies invasoras; Allelochemicals; Brazilian savanna; Natural herbicides; Invasive species; CIENCIAS BIOLOGICAS::BOTANICA